Blockchain and machine learning for e-healthcare systems - Balusamy, Balamurugan; Chilamkurti, Naveen, 1974-; Beena, T. Lucia Agnes; Poongodi, T. (Healthcare technologies series ;, 2020)
This edited book examines the application of blockchain technology and machine learning algorithms in various healthcare settings. This book covers the basic concepts of Blockchain and Machine Learning, and explores these issues with an eye on improving clinical outcomes and improving the patient's experience.